3D-printed resin for permanent/definitive restorations: meta-analysis for bond strength - Ki, Minjoo; Hayashi, Marc; Kim, Mijoo (PeerJ Materials Science, 2025)
Background Three-dimensional (3D) printing technologies have gained increasing popularity in restorative dentistry for fabricating polymer-based restorations. However, limited evidence exists regarding the bond strength between 3D-printed restorative materials and resin cements, particularly considering the effects of surface treatments and aging conditions. This meta-analysis aimed to synthesize the current knowledge on the adhesion of 3D-printed restorations to resin cements and identify areas for future research. Methodology A literature search was conducted in PubMed, Google Scholar, and Web of Science databases using the following keywords: “3D - printing”, “additive manufacturing”, “bond strength”, “resin cement”, “surface treatment”, and “aging”. Inclusion criteria were studies evaluating the bond strength of 3D-printed polymer restorative materials to resin cements, published in English, and with full-text availability. Data on bond strength values, failure modes, surface treatments, aging protocols, and material characterization were extracted and analyzed. Results Nine studies were included in the review. Digital light processing (DLP) and stereolithography (SLA) were the predominant 3D printing technologies. Airborne-particle abrasion (APA) with 50 µm aluminum oxide particles was used in five studies and significantly improved bond strengths compared to untreated controls. Chemical treatments such as silane coupling agents and universal adhesives containing 10-MDP were used in some studies and further enhanced adhesion when combined with APA. Thermocycling for 5,000 cycles, simulating 6 months of clinical service, was the most common aging protocol. Bond strengths generally decreased after aging, with some material and surface treatment combinations showing greater stability than others. Conclusions APA is an effective surface treatment method for improving the bond strength of 3D-printed polymer restorations to resin cement. The combination of mechanical treatment with chemical agents such as silane and 10-MDP provides additional benefits. Material composition, particularly the use of UDMA-based resins, significantly influences bond stability after aging. Standardized protocols for 3D-printing, post-processing, and testing methods are essential for consistent results. Further clinical investigations are needed to establish long-term performance guidelines and optimize bonding protocols for these innovative restorative materials.
Keywords: 3D-printed resin; Dental permanent restorations; Bond strength; Surface treatment; Restoration aging; Airborne-particle abrasion; Dental cement; Meta-analysis